1997
DOI: 10.1002/stem.150162
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral Stem Cell Gene Therapy

Abstract: Long-term in vivo gene transfer studies in mice have shown that recombinant murine retroviruses are able to infect murine hemopoietic stem cells with high efficiency. Taken together the results indicated that the proviral structure was present at high frequency in circulating hemopoietic cells resulting in significant expression levels. Because of the success of these murine studies, it was believed that gene therapy would soon be applicable to treat a wide variety of congenital or acquired human diseases asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 129 publications
0
21
0
Order By: Relevance
“…However, progress in the field of genetic transfer or modification into human longterm repopulating stem cells mediated by retroviral vectors has been blocked by the fact that levels of transfection are too low for any likely therapeutical benefit. 51,52 Several reports have demonstrated that an important reason for the low levels of transduction might involve certain incompatible features of the vectors used and the stem cells that they target.…”
Section: Retroviral Vectorsmentioning
confidence: 99%
“…However, progress in the field of genetic transfer or modification into human longterm repopulating stem cells mediated by retroviral vectors has been blocked by the fact that levels of transfection are too low for any likely therapeutical benefit. 51,52 Several reports have demonstrated that an important reason for the low levels of transduction might involve certain incompatible features of the vectors used and the stem cells that they target.…”
Section: Retroviral Vectorsmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44] Unfortunately, maneuvers for improving transduction in vitro, such as prolonging exposure to viral vectors, stimulating cell proliferation, or culturing on stromal cells, affect the phenotypic features of progenitor cells in undesirable ways. 45,46 To explore the concept of systemic gene delivery into areas of angiogenesis, we sought to use cellular vehicles naturally endowed with angiogiogenic tropism.…”
Section: Introductionmentioning
confidence: 99%
“…The observed superiority of amphotropic producer cells is in contradiction to previous data which suggested that ecotropic viral vectors mediate significantly higher transgene expression levels than amphotropic vectors. 29 Differences in the vectors and the transduction/transplantation protocol may explain these contrasting results.…”
Section: Discussionmentioning
confidence: 99%